2000
DOI: 10.1116/1.1314370
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of masks for electron-beam projection lithography

Abstract: Masks for electron projection lithography ͑EPL͒ require the use of thin membranes for either stencil or all membrane scattering masks. The processes of forming the printable patterns before or after the membrane etch step are compared for EPL stencil masks. Image size uniformity and image placement distortions are characterized and indicate, with appropriate process optimization, either process flow is viable for EPL mask manufacture. Image size uniformity within individual membranes has achieved Ͻ10 nm ͑3͒ wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2001
2001
2002
2002

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…[14] A similar axially dependent distortion is seen on continuous membrane masks. [13] The Sematech funded study also confirmed University of Wisconsin modeling results that pattern density gradients have the worst impact on IP. [15] For example, a subfield that was half-filled with a dense pattern (the other half being unpatterned) caused a large image placement distortion along the line of highest pattern density gradient.…”
Section: Pattern and Materials Requirementssupporting
confidence: 81%
See 2 more Smart Citations
“…[14] A similar axially dependent distortion is seen on continuous membrane masks. [13] The Sematech funded study also confirmed University of Wisconsin modeling results that pattern density gradients have the worst impact on IP. [15] For example, a subfield that was half-filled with a dense pattern (the other half being unpatterned) caused a large image placement distortion along the line of highest pattern density gradient.…”
Section: Pattern and Materials Requirementssupporting
confidence: 81%
“…Using the support ring provided almost 12 times better repeatability in absolute image placement than not using the ring. [13] This does not indicate that a support ring is necessary, but rather that the chucking format (the mask shape during use) should be standardized for EPL mask use.…”
Section: Pattern and Materials Requirementsmentioning
confidence: 98%
See 1 more Smart Citation
“…Image placement distortions result not only from the patterning of the membrane (IPD) but also from the differences in the chucking methodology between the e-beam writer, image placement measurement tool and the final exposure tool (out of plane distortions). Factors such as the clamping forces have been shown to lead to large out of plane distortions [7]. However, by using the subtractive technique all image placement caused external to pattern transfer are eliminated.…”
Section: Mask Patterning and Metrologymentioning
confidence: 99%
“…Improvements are needed in image size uniformity control across large mask areas and image placement control. First, tomask, and can distort based on the chucking forces [9]. Experiments performed for the Scalpel program show the feasibility of this concept,[10] and further experiments are underway to refine the requirements of the mask chucking scheme.All of the small format EPL masks at the MCoC have been formed using a wet etch removal of the silicon wafer to define the membranes.…”
mentioning
confidence: 99%